"Becoming Rather Than Being": Queer's Double-Edged Discourse as Deconstructive Practice. (October 2014) - Sewell, John Ike
This essay introduces the concept double-edged discourse (an oppositional discourse within another, larger oppositional discourse), relating it to the queer identity discourse that emerged within LGBTQ discourse in the wake of the AIDS crisis. The essay employs Laclau's logic of equivalence to examine queer's deployment as an empty signifier for the LGBTQ movement, further analyzing queer discourse in light of Badiou's concept of the Event and, finally, suggesting that queer's negotiation of identity is accomplished via its double edge and that queer be re-understood as deconstructive practice rather than as a collective identity per se.